Democracy in Latin America - Biato, Marcel (Emirates lecture series, 2011)
How to make a democracy a force for national unity and sense of common purpose, rather than a source of weakness and insecurity and lacking strong roots? This is the challenge the Middle East faces today as it seeks to make good on the promise of the 'Jasmine Revolution' sweeping through the region; a challenge that goes beyond the traditional Western concept of the region as one never ready for Democracy, either because of Islam or of a specific streak in Arab culture. This is the same challenge that Latin America faced for a long period of time and still continues to face today